Designing a Directional Acoustic Transmitter - Hladký David (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
In this paper the parametric transmission of sound through an amplitude-modulated ultrasonic wave, using automatic demodulation in a non-linear environment is discussed. Methods for the processing of the transmitted signal are presented; these techniques employ modified amplitude modulation to suppress the environmental effects, which otherwise distort the signal. A special emphasis is placed on the mathematical instruments describing the parametric sound beam transmission in a non-linear medium. Within our research, we fabricated a parametric speaker consisting of 50 ultrasonic acoustic transducers with the resonant frequency of 40 kHz. The functionality of the acoustic source was verified via measurement of the spatial radiation characteristics and through determination of the total harmonic distortion (THD). In order to control the parametric speaker, a digital element comprising a sampler, a transducer of the input transmitted signal, and a microcontroller to preprocess this signal and to facilitate the amplitude modulation of the ultrasonic carrier wave is designed. The applied algorithms were analyzed to establish their computational intensity; such an analysis enabled us to select a microprocessor basis suitable for the implementation of the signal processing algorithms.
Keywords: Parametric acoustic array; parametric loudspeaker; amplitude modulation; STM32F411